Peripheral complement interactions with amyloid β peptide: Erythrocyte clearance mechanisms - Brubaker, William D.; Crane, Andrés; Johansson, Jenny U.; Yen, Kevin; Garfinkel, Kristina; Mastroeni, Diego; Asok, Priya; Bradt, Bonnie; Sabbagh, Marwan; Wallace, Tanya L.; Glavis-Bloom, Courtney; Tenner, Andrea J.; et al. (Alzheimer's & dementia, 2017)
Although amyloid β peptide (Aβ) is cleared from the brain to cerebrospinal fluid and the peripheral circulation, mechanisms for its removal from blood remain unresolved. Primates have uniquely evolved a highly effective peripheral clearance mechanism for pathogens, immune adherence, in which erythrocyte complement receptor 1 (CR1) plays a major role. Multidisciplinary methods were used to demonstrate immune adherence capture of Aβ by erythrocytes and its deficiency in Alzheimer's disease (AD). Aβ was shown to be subject to immune adherence at every step in the pathway. Aβ dose-dependently activated serum complement. Complement-opsonized Aβ was captured by erythrocytes via CR1. Erythrocytes, Aβ, and hepatic Kupffer cells were colocalized in the human liver. Significant deficits in erythrocyte Aβ levels were found in AD and mild cognitive impairment patients. CR1 polymorphisms elevate AD risk, and >80% of human CR1 is vested in erythrocytes to subserve immune adherence. The present results suggest that this pathway is pathophysiologically relevant in AD.